Human resource management in the project-oriented organization - Turner, J. Rodney (John Rodney), 1953-; Huemann, Martina, 1969-; Keegan, Anne E. (Project Management Institute, 2008)
Human Resource Management (HRM) in project-oriented organizations is a relatively unexplored topic though it is essential to the success of the organization and its competitive advantage. Project-oriented organizations operate differently from classic business organizations in that they adopt temporary organizations in the form of projects and programs, therefore the HRM approach they adopt should support this unique structure. Human Resource Management in the Project-Oriented Organization takes a look at the multiple facets of HRM and how HRM should be applied in project-oriented organizations.